(untitled) (LEARNing Landscapes, 2010)
Michael Goldbloom explains how his education in Liberal Arts and Law has helped him pursue careers as varied as lawyer, newspaper publisher, community leader and now, Principal of Bishop’s University. He believes that learning good communication skills in elementary and secondary school as well as interacting with others in an effective and respectful way are key elements to any future career. His family’s emphasis on education and community involvement was critically important to the educational and career choices he made. He makes a case for the model of the small university as an ideal community for young people to develop their academic skills, participate in sports or artistic pursuits, contribute to student life and forge relationships with fellow students and professors. Lastly, Mr. Goldbloom supports the idea that entrepreneurship should be a key ingredient in postsecondary education, not just for business students, but for all students to have the ability to manage their careers.